2019
DOI: 10.1111/dom.13853
|View full text |Cite
|
Sign up to set email alerts
|

Dulaglutide is an effective treatment for lowering HbA1c in patients with type 2 diabetes regardless of body mass index

Abstract: Aim To assess the relationship between baseline body mass index (BMI) and glycaemic control in dulaglutide‐treated patients, a post hoc analysis was conducted on HbA1c and baseline BMI data from eight AWARD studies, with a total of 5770 patients. Materials and methods Changes from baseline in HbA1c data from patients treated with 1.5 mg or 0.75 mg dulaglutide, active comparator or placebo, were analyzed in each study (AWARD‐1 to −6, −8 and − 9) at approximately 6 months (26, 24 and 28 weeks, respectively). Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
2
3
1
Order By: Relevance
“…These results are consistent with the AWARD trials, which showed that neither baseline BMI nor duration of diabetes was associated with patients' responses to dulaglutide (3)(4)(5). Previous AWARD studies showed that treatment with dulaglutide results in HbA 1c reduction early in treatment in populations of study patients at lower risk for CVD (10)(11)(12)(13)(14).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are consistent with the AWARD trials, which showed that neither baseline BMI nor duration of diabetes was associated with patients' responses to dulaglutide (3)(4)(5). Previous AWARD studies showed that treatment with dulaglutide results in HbA 1c reduction early in treatment in populations of study patients at lower risk for CVD (10)(11)(12)(13)(14).…”
Section: Discussionsupporting
confidence: 87%
“…Glucagon-like peptide-1 (GLP-1) receptor agonists are a class of glucose-lowering drugs used to treat type 2 diabetes and include dulaglutide. Post hoc analysis of the Assessment of Weekly AdministRation of LY2189265 in Diabetes (AWARD) trials suggests that the 6-month glycemic effect of dulaglutide is independent of BMI and duration of diabetes (3)(4)(5). Whether these characteristics or the presence of microvascular disease affects glucose lowering during short-or long-term therapy remains unknown (6).…”
mentioning
confidence: 99%
“…Results of our analysis comparing BMI subgroups did not differ from those of the post-hoc analysis of the AWARD trials, showing no significant differences in HbA1c reduction levels among the subgroups ( 24 ). However, the mean baseline BMI levels in the AWARD trials, ranging between 31.2 and 33.3 kg/m 2 , were greater compared with the corresponding levels of 27.99 kg/m 2 in our study.…”
Section: Discussioncontrasting
confidence: 49%
“…In addition, there is no moderating effect of BMI on HbA1c reduction with GLP1 receptor agonists, which appears to be similar in obese and lean patients. This latter result is in line with reports from randomized clinical trials 26 and cohort studies 27 . The effect of initial HbA1c on the incidence of treatment failure depends on the definition of success: if success is defined as the attainment of pre‐defined target HbA1c levels, a higher HbA1c level should be expected to be associated with a higher proportion of failures; on the other hand, if success is defined as a pre‐determined absolute reduction of HbA1c levels, such a target could be easier to reach in patients with higher baseline HbA1c.…”
Section: Discussionsupporting
confidence: 93%